A qualitative study of Ghanaian pediatric oncology nurses' care practice challenges - Ruth Nimota Nukpezah; Fatemeh Khoshnavay Fomani; Marzieh Hasanpour; Alireza Nikbakht Nasrabadi (BMC, 2021)
Abstract Background Pediatric cancer is a global problem, and some studies have emphasized that nurses caring for these children experience work-related challenges. This has caused many children diagnosed with cancer to have a prolonged hospital stay and suffer unnecessary pain. However, there is insufficient documentary evidence on this issue. This study aims to explore and understand the challenges faced by pediatric oncology nurses in caring for children in Ghana. Methods An exploratory qualitative research design study was conducted from August 2019 to April 2020. The study was conducted at the pediatric oncology unit which is located at the Tamale Teaching Hospital (TTH), Ghana. The study was conducted among 14 Ghanaian pediatric oncology nurses who were purposively sampled. A semi-structured interview guide was used to collect data. The interviews were recorded, transcribed verbatim, and analyzed inductively using Elo and Kyngas content analysis approach. The criteria proposed by Guba and Lincoln were used to ensure the validity of the study. Results From the analysis of participants transcripts, eight subcategories emerged from two major categories. The subcategories were; time-consuming care, low job motivations, inadequate logistics, work stress, reduced labour force, low knowledge level, lack of teamwork and the perception of contracting cancer. Conclusions The results point to several organizational and personal constraints experienced by the nurses who work at the pediatric oncology ward. It is hoped that by addressing these challenges, it would lead to further improvement in the care that is provided to children with cancer. There is the need for the administrative managers of hospitals, government and other stakeholders to invest in human, material and financial resources for delivering childhood cancer care services.